Smart Phone Apps and Maternal Child Nursing. Issue 5 (September 2017) - N/A,
Abstract : Our guest editor for this special topics series on smart phone applications and maternal child nursing, Dr. Logsdon, offers an overview and suggestions for the role of the nurse.